1990
DOI: 10.2337/diab.39.11.1373
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Insulin on Oxidation of Intracellularly and Extracellularly Derived Glucose in Patients With NIDDM: Evidence for Primary Defect in Glucose Transport and/or Phosphorylation but Not Oxidation

Abstract: Insulin-stimulated glucose oxidation is decreased in patients with non-insulin-dependent diabetes mellitus (NIDDM). It is not known whether this decrease is due to a primary defect in the oxidative pathway or is secondary to impaired glucose transport and/or phosphorylation. To address this issue, glucose oxidation was measured under steady-state conditions at low (approximately 270 pmol) and high (approximately 17 mumol) insulin concentrations in seven patients with NIDDM and seven healthy nondiabetic subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…However, an alteration in intracellular glucose metabolism presumably would not influence glucose uptake if glucose transport/phosphorylation remained rate limiting. Data have been presented arguing both for (41,42) and against (43) transport/phosphorylation as the rate-limiting step for glucose uptake in NIDDM during insulin infusion. Third, although transport may remain rate limiting, hyperglycemia and hyperinsulinemia may facilitate glucose uptake via different transporters.…”
Section: Discussionmentioning
confidence: 99%
“…However, an alteration in intracellular glucose metabolism presumably would not influence glucose uptake if glucose transport/phosphorylation remained rate limiting. Data have been presented arguing both for (41,42) and against (43) transport/phosphorylation as the rate-limiting step for glucose uptake in NIDDM during insulin infusion. Third, although transport may remain rate limiting, hyperglycemia and hyperinsulinemia may facilitate glucose uptake via different transporters.…”
Section: Discussionmentioning
confidence: 99%
“…Defects in facilitative glucose transport have been implicated in the pathogenesis of type 2 diabetes [20][21][22]. The gene encoding the glucose transporter protein solute carrier family 2, facilitated glucose transporter, member 10 (SLC2A10, previously known as glucose transporter 10 [GLUT10]), lies within the NIDDM3 susceptibility region, and is a novel facilitative glucose transporter that is highly expressed in the liver and pancreas, the two major organs involved in maintaining blood glucose homeostasis [23].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Bonnadonna et al, using a novel isotope tracer and limb balance approach (5), and Kelley et al (6), analyzing rate constants for [ 18 F]2-deoxyglucose uptake during positron emission scanning, have provided evidence for separate defects in both transport and glucose phosphorylation in type 2 diabetes. However, under conditions of stimulated glucose flux, investigators have found that free glucose and glucose-6-phosphate do not accumulate in skeletal muscle (4,(7)(8)(9) and that metabolism within intracellular pathways can be normalized (10)(11)(12). These latter data indicate that transport system defects likely predominate in mediating insulin resistance.…”
Section: Introductionmentioning
confidence: 99%